Impact of Novel Guidelines on Multifactorial Control and Its Association with Mortality in Adult Patients with Hypertension and Newly Diagnosed Type 2 Diabetes: A 4-Year Prospective Multicenter Study - Ngoc-Thanh-Van Nguyen; Hoa Ngoc Chau; Nam Hoai Le; Hai Hoang Nguyen; Hoai-An Nguyen (International Journal of Endocrinology)
Background and Rationales. Hypertensive patients with newly diagnosed diabetes are associated with heightened risks for cardiovascular events. Yet endorsement of state-of-the-art guidelines with more stringent goals poses significant challenges in obtaining multifactorial control. This study aimed to illustrate the impact of novel targets on achieving simultaneous control overtime and its association with mortality. Methods. This prospective, observational study involved adult hypertensive patients with newly diagnosed type 2 diabetes mellitus at two university hospitals in Vietnam. The median time of follow-up was 4 years (August 2016–August 2020). The primary outcome was time to all-cause mortality. Results. 246 patients were included with a mean age of 64.5 ± 10.4. 58.5% were females. 64.2% were categorized as high risk. At baseline, ischemic heart disease, dyslipidemia, and chronic kidney disease (CKD) were present in 54.9%, 67.1%, and 41.1% of patients. Renin–angiotensin–aldosterone inhibitor, metformin, and statin were prescribed in 89.8%, 66.3%, and 67.1%. Among three risk factors, LDL-c control was the hardest to achieve, increasing from 5.7% to 8.5%. In contrast, blood pressure control decreased from 56.1% in 2016 to 30.2% in 2020, when the second wave of COVID-19 hit our nation. While contemporary targets resulted in persistently low simultaneous control at 1.2%, significant improvement was observed with conventional criteria (blood pressure  < 140/90 mmHg, HbA1c < 7%, LDL-c < 70 mg/dl), increasing from 14.6% to 33.7%. During follow-up, the mortality rate was 24.4 events per 1000 patient-years, exclusively in patients with early newly diagnosed diabetes. Improving control overtime, not at baseline, was associated with less mortality. Conversely, age >75 years (HR = 2.6) and CKD (HR = 4.9) were associated with increased mortality. Conclusion. These findings demonstrated real-world difficulties in managing hypertension and newly diagnosed diabetes, especially with stringent criteria from novel guidelines. High-risk profile, high mortality, and poor simultaneous control warrant more aggressive cardiorenal protection, focusing more on aging CKD patients with early newly diagnosed diabetes.